The predictive value of a body shape index as a novel obesity metric for cancer risk: a systematic review and meta-analysis - Liu, Hui; Fu, Hongjia; Wang, Zengyu; Yao, Zhicui; Wang, Qi; Sui, Aixia; Meng, Yuan; Xu, Xin; Shen, Yongqing; Liu, Wei (Frontiers in Nutrition, 2025)
BackgroundThe A Body Shape Index (ABSI), a metric assessing visceral adiposity distribution by integrating height, weight, and waist circumference (WC), remains a subject of debate regarding its predictive value for diverse cancer risks. This study aims to assess the predictive capacity of ABSI for cancer utilizing systematic review and meta-analysis methodologies, contrasting its performance against conventional anthropometric indices such as body mass index (BMI) and WC.MethodsA comprehensive search of PubMed, Web of Science, and Embase databases was performed from inception through April 27, 2025, to identify observational studies examining associations between ABSI and cancer. Random-effects or fixed-effects models were employed to calculate pooled hazard ratio (HR), odds ratio (OR), and area under the receiver operating characteristic curve (AUC) metrics with corresponding 95% confidence interval (CI), selected according to heterogeneity thresholds. Furthermore, heterogeneity and publication bias were also assessed.ResultsThis study included 10 studies (7 cohort studies and 3 cross-sectional studies) with a total sample size of 1,520,762 participants. Results indicated that each one-standard-deviation increase in ABSI was associated with an 8% increase in overall colorectal cancer (CRC) risk, with a significant 13% increase in men and a 6% increase in women. In terms of predictive efficacy, ABSI (pooled AUC = 0.66) outperformed other anthropometric indicators, though in men, each one-standard-deviation increase in ABSI was associated with a significantly lower risk increase by 7% compared to WC. Additionally, no significant association was found between ABSI and the risk of prostate or breast cancer.ConclusionABSI demonstrates remarkable specificity for specific cancer types in cancer risk prediction. It independently predicts CRC risk, particularly in identifying high-risk male populations with central adiposity, serving as a beneficial supplementary tool to WC rather than a substitute. Available evidence does not support the routine application of ABSI for predicting prostate or breast cancer risks. Future studies with larger and more diverse samples are necessary to further verify the effectiveness of ABSI and strengthen its evidential basis.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251047230.